La « recherche-formation », une contribution aux approches collaboratives en formation initiale d’enseignants de langues - Dominique Macaire (Recherches en didactique des langues et des cultures)
Forming in and by the research in the domains of the teacher education and training is the aim of the ESPÉ, which are nowadays redesigned into Inspé, as we cannot train tomorrow's teachers with yesterday's resources. New more collective methodologies of observation and analysis are required in a complex school context, both in the light of the questions emerging in language didactics and of the blind spots of the professional practices. A main issue for teacher education then consists in making readable works written in the paradigm of plurilingualism (Herdina et Jessner, 2002), but also in co-producing them in an established collective way (Behra et Macaire, 2019). This is also the meaning of a "research-based teacher education" (Macaire, 2019), which is characterized by its two-way collaborative dimension, to and from education, as well as to and from research. The knowledge resulting from their collaborative work is necessarily mixed and multifaceted. It reveals new “spaces for interest-sharing” (Akrich et al., 1991), or “spaces for co-interest” (Macaire, 2019). According to a theoretical framework of collaborative “research-based teacher education”, we will analyse the ways it develops in the light of the formative and research challenges, combined with major dynamic scientific issues like plurilingualism.research-based teacher education, professional development, research methodology in language didactics, collaborative research